TANGGUNG JAWAB BBPOM DALAM PENGAWASAN PEREDARAN JAMUTRADISIONAL DI PEKANBARU BERDASARKANPERA- TURANBADAN PENGAWAS OBAT DANMAKANANNOMOR 12 TAHUN 2018TENTANG ORGANISASI DANTATA KERJA UNITPELAKSANATEKNISDILINGKUNGANBADAN PENGAWASOBAT DAN MAKANAN - Viky Anggara Putra; Dessy Artina; Evi Deliana HZ (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2022)
Based on the regulation of the drug and food regulatory agency number 12of 2018 concerning the organization and work procedures of technicalimplementing units within the drug and food regulatory agency. Based onresearch by researchers at the UPT BBPOM Pekanbaru, it is still not optimal interms of implementing supervision and Regulation of the Minister of Health of theRepublic of Indonesia Number 15 of 2018 concerning the Implementation ofComplementary Traditional Health Services, this regulation is technical in theimplementation related to complementary traditional health services. Regulationof the Minister of Health of the Republic of Indonesia Number 15 of 2018Concerning the Implementation of Complementary Traditional Health Services, itis necessary if a study both philosophically, sociologically and juridically in theimplementation of complementary traditional medicine in Pekanbaru is inaccordance with these regulations. This type of research can be classified into thetype of sociological legal research.The conclusions that can be obtained from the research results are First,the responsibility of the Pekanbaru City Drug and Food Supervisory Agency(BBPOM) regarding the supervision of traditional herbal medicine productionbased on BPOM agency regulations number 12 of 2018 and Permenkes number15 of 2018 in Pekanbaru, namely starting from issuing permits to supervision inthe product distribution Second, the Inhibiting Factors for Oversight of thePekanbaru City Drug and Food Control Center regarding the production oftraditional herbal medicine Third, the efforts made by the Pekanbaru City Drugand Food Control Center to supervise and control the production of traditionalherbal medicine in Pekanbaru, namely issuing distribution permits for productsand certificates in accordance with standards and requirements for safety,efficacy/benefits, and quality, as well as drug and food testing in accordance withstatutory provisionsKeywords: Responsibility, Traditional Medicine, Traditional Health.